The Evolution of Hypervelocity Supernova Survivors and the Outcomes of Interacting Double White Dwarf Binaries - Ken J. Shen (The Astrophysical Journal)
The recent prediction and discovery of hypervelocity supernova survivors has provided strong evidence that the “dynamically driven double-degenerate double-detonation” (D ^6 ) Type Ia supernova scenario occurs in nature. In this model, the accretion stream from the secondary white dwarf (WD) in a double WD binary strikes the primary WD violently enough to trigger a helium shell detonation, which in turn triggers a carbon/oxygen core detonation. If the secondary WD survives the primary’s explosion, it will be flung away as a hypervelocity star. While previous work has shown that the hotter observed D ^6 stars can be broadly understood as secondaries whose outer layers have been heated by their primaries’ explosions, the properties of the cooler D ^6 stars have proven difficult to reproduce. In this paper, we show that the cool D ^6 stars can be explained by the Kelvin–Helmholtz contraction of helium or carbon/oxygen WDs that underwent significant mass loss and core heating prior to and during the explosion of their WD companions. We find that the current population of known D ^6 candidates is consistent with ∼2% of Type Ia supernovae leaving behind a hypervelocity surviving companion. We also calculate the evolution of hot, low-mass oxygen/neon stars and find reasonable agreement with the properties of the LP 40–365 class of hypervelocity survivors, suggesting that these stars are the kicked remnants of near-Chandrasekhar-mass oxygen/neon WDs that were partially disrupted by oxygen deflagrations. We use these results as motivation for schematic diagrams showing speculative outcomes of interacting double WD binaries, including long-lived merger remnants, Type Ia supernovae, and several kinds of peculiar transients.